Keeping pace with the healthcare transformation: a literature review and research agenda for a new decade of health information systems research - Nadine Ostern; Guido Perscheid; Caroline Reelitz; Jürgen Moormann (Electronic Markets, 2021)
Background Accelerated by the coronavirus disease 2019 (Covid-19) pandemic, major and lasting changes are occuring in healthcare structures, impacting people's experiences and value creation in all aspects of their lives. Information systems (IS) research can support analysing and anticipating resulting effects. Aim The purpose of this study is to examine in what areas health information systems (HIS) researchers can assess changes in healthcare structures and, thus, be prepared to shape future developments. Method A hermeneutic framework is applied to conduct a literature review and to identify the contributions that IS research makes in analysing and advancing the healthcare industry. Results We draw an complexity theory by borrowing the concept of 'zooming-in and out', which provides us with a overview of the current, broad body of research in the HIS field. As a result of analysing almost 500 papers, we discovered various shortcomings of current HIS research. Contribution We derive future pathways and develop a research agenda that realigns IS research with the transformation of the healthcare industry already~under way.
Keywords: I0; I1; 620; Healthcare; Health information systems research; Research agenda